Design and modeling of the passive residual heat removal system for VVERs. (September 2016) - Ayhan, Hüseyin; Sökmen, Cemal Niyazi
Highlights: The new geometrical design of passive residual heat removal system for VVER type reactors is developed. This original design can remove up to 2% of reactor nominal power in case of station blackout even in LOCA. Designed system is investigated by using RELAP5 code under several boundary and operating conditions. Abstract: The results and effects of the Fukushima Daiichi accident show that the passive safety systems, which require no user input in order to operate, are very significant in nuclear industry. Even after stopping the reactor, heat dissipation remains a primary concern. If the reactor is not properly managed after shutdown, residual heat may cause catastrophic failures. The passive residual heat removal system (PRHRS) is designed to increase the inherent safety features of Nuclear Power Plants (NPP). In the present study, thermal hydraulic performance of the PRHRS of VVER type NPP is investigated using RELAP5 MOD3.4 (developed by Innovative Systems Software) system code. The PRHRS is designed to remove decay heat when normal heat removal system is not available and it consists of steam generator secondary side, a heat exchanger cooling by atmospheric air, and corresponding pipes, valves and air gates. In accident conditions, residual heat is transferred to the ambient air by natural circulation in both steam and air cycles of PRHRS. In the part which include analytical calculations of this study, geometric design parameters of PRHRS was investigated for 5.50 MW heat capacity. Selected system parameters, which are found by performing analytical modeling, are tested and analyzed with RELAP5 code and compared with the analytical results. Steady-state behavior of the system has been simulated, and cooling capacity of PRHRS has been investigated during station blackout scenario (including loss of coolant accident case). The results of steady-state behavior obtained by using RELAP5 code show that the PRHRS is able to take residual heat away from the primary coolant system.